Model Predictive Control of Modular Multilevel Converter with High Number of Submodules - Kadhum, Hussein; Alan, Watson; Saleh, Beeond M.; Marco, Rivera; Pericle, Zanchetta; Patrick, Wheeler (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
This paper proposes a Level Model Predictive Control strategy combined with a pre-processing sorting algorithm to address the processing time issue of predictive control for Modular Multilevel Converters (MMCs) with hundreds of submodules. Five control objectives are optimized in a single cost function, resulting in good performance under a range of operating conditions, validated using PLECs simulation results.